Mission time in Warburton : an exhibition exploring aspects of the Warburton Mission History, 1933-1973. - Tjulyuru Regional Arts Gallery (Warburton, W.A. : WAP Press [for the] Tjulyuru Regional Arts Gallery, Tjulyuru Cultural and Civic Centre, 2002)
Book to accompany 2002 exhibition 'Mission Time in Warburton' which aimed to reflect views and perceptions of Warburton and wider Ngaanyatjarra community about their experiences with Warburton Mission between 1933 and 1973; consists of paintings, stories and memories, documents and photographs; history of language work; find-a-word puzzles; hymns and songs; history and impact of Mission; chronology of key dates; notes on artists and contributors.
Keywords: Tjulyuru Regional Arts Gallery -- Exhibitions; Warburton Ranges Mission (W.A) -- History; Warburton Ranges Mission (W.A.) -- Exhibitions; Aboriginal Australians -- Western Australia -- Warburton Ranges -- Art -- Exhibitions; Aboriginal Australians -- Missions -- Western Australia -- Warburton Ranges -- Exhibitions; Aboriginal Australians -- Missions -- Western Australia -- Warburton Ranges -- History; Religions - Christianity - Missions; Ngaanyatjarra people (A38) (WA SG51-08); Religions - Christianity - Missionaries; Art - Economic aspects - Markets - Market places; Religions - Christianity - Missions - United Aborigines Mission; History; Milyirrtjarra / Warburton (Central WA SG52-09)